Neurogliaform cells mediate feedback inhibition in the medial entorhinal cortex - Szocs, Szilard; Henn-Mike, Nora; Agocs-Laboda, Agnes; Szabo-Meleg, Edina; Varga, Csaba (Frontiers in Neuroanatomy, 2022)
The layer I of the medial entorhinal cortex (MEC) contains converging axons from several brain areas and dendritic tufts originating from principal cells located in multiple layers. Moreover, specific GABAergic interneurons are also located in the area, but their inputs, outputs and effect on local network events remain elusive. Neurogliaform cells are the most frequent and critically positioned inhibitory neurons in layer I. They are considered to conduct feed-forward inhibition via GABAA and GABAB receptors on pyramidal cells located in several cortical areas. Using optogenetic experiments, we show that layer I neurogliaform cells receive excitatory inputs from layer II pyramidal cells, thereby playing a critical role in local feedback inhibition in the MEC. We also found that neurogliaform cells are evenly distributed in layer I and do not correlate to the previously described compartmentalization (“cell islands”) of layer II. We conclude that the activity of neurogliaform cells in layer I is largely set by layer II pyramidal cells through excitatory synapses, potentially inhibiting the apical dendrites of all types of principal cells in the medial entorhinal cortex.